pensamento computacional e a plataforma Thunkable no ensino de juros simples nos anos finais do ensino fundamental - Oliveira, Cleunice de (2024)
This dissertation, part of the research line Pedagogical Innovations for Teaching Science and Mathematics, aims to investigate to what extent Computational Thinking, with the support of the Thunkable platform, can contribute to the teaching of simple interest in the Final Years of Elementary School, considering the daily lives and social context of students. To this end, the works of Seymour Papert and his Constructionist Learning Theory and official documents, such as the BNCC, the Gaucho Curricular Reference and the Reference Curriculum of the Territory of Soledade-RS, were used as theoretical contributions. In order to validate the research, a sequence of activities organized based on constructionism and the use of the Thunkable platform was applied to an 8th grade class of Elementary School in a school in the municipal education network of Soledade/RS. To obtain the data, the records of the research teacher and the questionnaires answered by the students were used as data collection instruments. The resulting data allowed us to indicate that, a priori, the statement that Computational Thinking, through the use of the Thunkable Platform, contributes to the teaching of simple interest in the Final Years of Elementary School is valid, as students take on the leading role in their own learning and create their own applications, based on their interests. It is worth noting that, based on the feedback from the students who participated in the research, creating an environment that is conducive to learning is essential. In line with this research, the educational product "Computational Thinking Activities for Teaching Simple Interest Using the Thunkable Platform" was developed, which consists of a supplementary educational material organized into eight meetings, each lasting two to three hours. This was designed to enhance students' perceptions when researching, discussing and applying the mechanisms that govern compound interest, simple interest, interest rates, the viability of making certain financial investments and the best way to do so; and the relationship between money and time, manipulating an authoring environment. The proposed activities showed potential to be addressed by other teachers, in the most diverse school environments, and also in addressing the various related topics. This material is available for free access on the website of the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo (http://www.upf.br/ppgecm), as well as on the eduCapes Portal (http://educapes.capes.gov.br/handle/capes/748497).